ANALISIS KONSEP HIRFAH SEBAGAI INDIKATOR KAFAAH DALAM PEMBENTUKAN KELUARGA IDEAL PERSPEKTIF HUKUM KELUARGA ISLAM - M. Hidayat; Azhar Azhar; Kamaliah. R (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
The high divorce rate in Indonesia, particularly due to emotional conflicts and economic pressures, highlights the urgency of examining key factors of family resilience. One of these is hirfah (profession), which plays a strategic role within the concept of kafaah in shaping the ideal family. This study aims to analyze the role of hirfah as an indicator of kafaah in modern social contexts and its relevance for building families characterized by sakinah, mawaddah, and rahmah according to Islamic Family Law. The method employed is library research with descriptive-analytical analysis of classical and contemporary fiqh literature, complemented by relevant academic studies. The findings reveal that a lawful, proper, and stable profession is not only crucial for economic stability but also serves as a symbol of responsibility, social dignity, and psychological readiness for marriage. Thus, hirfah as part of kafaah plays a significant role in fostering a resilient and harmonious family and remains relevant as a reference in premarital counseling and contemporary Islamic family policies.